A multi-channel system for use in cardiac electrophysiologic studies - Wyatt, Barry Neil (Division of Biomedical Engineering, 2018)
The location of accessory pathways in Wolff-Parkinson-White syndrome patients is performed manually during open heart surgery at Groote Schuur Hospital, using a hand-held roving electrode. This manual procedure is slow and tedious, prolonging the operation and the time for which the patient remains on cardiac bypass. A multichannel electrogram acquisition and display system with a storage facility would significantly reduce the time taken and improve the reliability of locating the accessory pathways. Having considered a number of currently available cardiac mapping systems it was decided that a new system be developed for specific application within Groote Schuur Hospital. The main design goals of this system are to improve accuracy, increase reliability and enhance the speed of the entire mapping procedure with direct benefit to staff and patients. The system is based on an IBM compatible computer and allows for the acquisition of a maximum of thirty-two electrogram inputs. A typical configuration would acquire twenty epicardial, two references (one each from atrium and ventricle), one roving electrode and two surface lead signals. The epicardial signals are obtained from a custom-built electrode belt which is placed around the heart over the atrioventricular groove. The project includes the development of front-end hardware and software for processing, display and storage of electrogram signals. The relative activation times of the signals are displayed under software control in order to facilitate the location of any accessory pathway(s).